Literature Review: Curcumin Alternative Therapy For Breast Cancer - Nurayuni, Tiara (Sean Institute, 2024)
Breast cancer is a serious disease that affects millions of people worldwide every year. Risk factors include gender, age, family history, and genetic factors. Although there are treatment methods such as surgery, radiation, and chemotherapy, breast cancer management often brings various physical, social, psychological, and financial problems for patients. Therefore, alternative treatments like the use of herbal plants, particularly compounds like curcumin, have been researched as potential anticancer agents with minimal side effects. The aim of this study is to explore in depth the potential of curcumin in breast cancer. This article is compiled from various databases, including Pubmed and Google Scholar, using the keywords